2018
DOI: 10.5606/archrheumatol.2018.6704
|View full text |Cite
|
Sign up to set email alerts
|

Association of MICA Alleles and Human Leukocyte Antigen B in Turkish Patients Diagnosed With Behçet's Disease

Abstract: Objectives: This study aims to investigate whether or not MHC class I polypeptide-related sequence A (MICA) polymorphisms are associated with the susceptibility to Behçet's disease (BD) in a Turkish population. Patients and methods: The study included 38 Turkish BD patients (20 males, 18 females; mean age 34±10.9 years) and 51 ethnically matched healthy controls (30 males, 21 females; mean age 36±12.8 years). MICA and human leukocyte antigen B (HLA-B) alleles were determined in all subjects by using the Lumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Activating receptors KIR2DS1 and KIR2DS2 are implicated in the pathogenesis of autoimmune diseases such as in the examples of RA and psoriasis (332,333). The expression of the ligands of the activating receptors, such as MICA also contributes to the disease pathogenesis such that alternated receptor affinty may lead to activaiton in predisposed individuals, observed in various autoimmune diseases including RA, BD and type 1 diabetes (334)(335)(336). Finally, certain KIR/HLA combinations reduce the activation threshold of the NK cells and can be protective against some infections, while the same KIR/HLA combination may also predispose autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Activating receptors KIR2DS1 and KIR2DS2 are implicated in the pathogenesis of autoimmune diseases such as in the examples of RA and psoriasis (332,333). The expression of the ligands of the activating receptors, such as MICA also contributes to the disease pathogenesis such that alternated receptor affinty may lead to activaiton in predisposed individuals, observed in various autoimmune diseases including RA, BD and type 1 diabetes (334)(335)(336). Finally, certain KIR/HLA combinations reduce the activation threshold of the NK cells and can be protective against some infections, while the same KIR/HLA combination may also predispose autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Eyerci et al reported the MICA*006 (MICA-A6) and MICA*009 alleles were associated with BD susceptibility in the HLA-B*51 positive Turkish population. [30]. MICA-A5.1 was indicated a negative correlation with ocular lesions and iridocyclitis in BD patients [31].…”
Section: Micamentioning
confidence: 87%
“…MICA * 009 allele has also been found in a high frequency in melanoma patients compared with controls (51). Additionally, both MICA * 009 and MICA * 004 (MICA * A6) have been associated with Behcet disease (18,(52)(53)(54)(55)(56) and rheumatoid arthritis (57). However, this variant was less frequent in patients with colorectal cancer (58), indicating that MICA alleles play a different role depending on the type of cancer, possibly due to cellular and molecular mechanisms that are particularly associated with different types of tumors.…”
Section: Discussionmentioning
confidence: 99%